A Longitudinal Study of IPV Victimization Among Sexual Minority Youth. Issue 5 (March 2019) - Whitton, Sarah W.; Newcomb, Michael E.; Messinger, Adam M.; Byck, Gayle; Mustanski, Brian
Although intimate partner violence (IPV) is highly prevalent among lesbian, gay, bisexual, and transgender (LGBT) youth, little is known regarding its developmental patterns, risk factors, or health-related consequences. We examined IPV victimization in an ethnically diverse community-based convenience sample of 248 LGBT youth (aged 16-20 at study outset) who provided six waves of data across a 5-year period. Results from multilevel models indicated high, stable rates of IPV victimization across this developmental period (ages 16-25 years) that differed between demographic groups. Overall, 45.2% of LGBT youth were physically abused and 16.9% were sexually victimized by a dating partner during the study. Odds of physical victimization were 76% higher for female than for male LGBT youth, 2.46 times higher for transgender than for cisgender youth, and 2 to 4 times higher for racial-ethnic minorities than for White youth. The prevalence of physical IPV declined with age for White youth but remained stable for racial-ethnic minorities. Odds of sexual victimization were 3.42 times higher for transgender than for cisgender youth, 75% higher for bisexual or questioning than for gay or lesbian youth, and increased more with age for male than female participants. Within-person analyses indicated that odds of physical IPV were higher at times when youth reported more sexual partners, more marijuana use, and lower social support; odds of sexual IPV were higher at times when youth reported more sexual partners and more LGBT-related victimization. In prospective analyses, sexual IPV predicted increased psychological distress; both IPV types marginally predicted increased marijuana use.